Designing public open spaces within 1km of UP-PGH for the COVID-19 pandemic and wellbeing - See, Karina Anne; Navarra, Nappy L.; Rosell, Auriga Joy B. (Quezon City College of Architecture, University of the Philippines Diliman, 2021)
The ongoing COVID-19 pandemic has highlighted the many benefits of public open spaces in urban areas. They serve as safer places against airborne viral transmission, while also providing many benefits to human wellbeing during a time when tight indoor spaces are avoided. However, here in Metro Manila, this research finds that the public spaces are not being maximized due to various reasons, including the lack of COVID-19 precautions. This research aims to propose general landscape architectural designs and guidelines for six types of public open spaces within 1 kilometer of the University of the Philippines-Philippine General Hospital in Manila, Philippines (UP-PGH). The research took three major steps to gather relevant data to meet the research goal. (1) Data related to COVID-19 transmission in the built environment and how landscape design affects wellbeing was gathered and reviewed to come up with a theoretical framework. (2) The public open spaces found within 1km of UP-PGH were mapped and classified into six typologies, and the general environmental conditions were analyzed by means of literature review, in-person site visits, and interviews with community members. (3) the needs of community members (in terms of wellbeing before and during the pandemic) were learned through reviewing secondary surveys and interviews with community members. The research findings were synthesized in three forms (1) Landscape architectural design recommendations for three hypothetical future scenarios were formulated, following an exploratory scenario planning approach. (2) Landscape architectural site development plans were generated for each typology in the median scenario as a proof-concept for the design recommendations. (3) guidebook was developed containing all the findings for easier communication with potential beneficiaries of this research. The results of this research can serve as a guide for interested people and become a stepping stone towards improving the wellbeing of Filipinos during the COVID-19 pandemic.
includes appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Landscape architecture; Open spaces; Public spaces